1989
DOI: 10.1128/aem.55.11.2954-2959.1989
|View full text |Cite
|
Sign up to set email alerts
|

Formation of delta 2- and delta 3-cholenoic acids from bile acid 3-sulfates by a human intestinal Fusobacterium strain

Abstract: We isolated two strains of an unnamed Fusobacterium species from human intestinal microflora, which stereospecifically transformed bile acid 3-sulfates into C-3-unsubstituted, ring A-unsaturated bile acids. Both 3aand 3,-sulfates of 5p-bile acids were metabolized to A3-5I-cholenoic acids; 3,8-sulfates of 5a-bile acids were converted into a mixture of A2-5a-bile acids and 3a-hydroxy-5a-bile acids, whereas 3at-sulfates of 5a-bile acids were left intact. Unsulfated bile acids were not transformed into unsaturated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Furthermore, the significant increase in the abundance of Fusobacterium afforded by ezetimibe was positively correlated with AST and negatively correlated with butyric acid. A previous study stated that Fusobacterium was responsible for bile acid desulfation ( Robben et al, 1989 ), which further indicated the possible links between Fusobacterium and liver dysfunction. Previous evidence suggested a potential active role for Fusobacterium ( Fusobacteria ), specifically F. nucleatum , in colorectal cancer ( Hussan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, the significant increase in the abundance of Fusobacterium afforded by ezetimibe was positively correlated with AST and negatively correlated with butyric acid. A previous study stated that Fusobacterium was responsible for bile acid desulfation ( Robben et al, 1989 ), which further indicated the possible links between Fusobacterium and liver dysfunction. Previous evidence suggested a potential active role for Fusobacterium ( Fusobacteria ), specifically F. nucleatum , in colorectal cancer ( Hussan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 90%
“…However, little is known about the role of gut bacteria in carrying such a reaction. Bacterial genera responsible for BA desulfation include Clostridium (90, 91), Peptococcus (92), and Fusobacterium (93). To date, this reaction mechanism has not been unleashed, and the enzymes have not been characterized.…”
Section: Impact Of Gut Microbiota On Cholesterol Metabolismmentioning
confidence: 99%
“…In the gut, Fusobacterium contributes to the production of butyrate and the metabolism of bile acids [ 47 , 48 , 49 , 50 ]. Short-chain fatty acids are the metabolites of various nutrients fermented by particular microorganisms in the gut [ 51 ].…”
Section: Discussionmentioning
confidence: 99%